The Public Goods Theory and the Paradigm of Public Sector Economics - Kargol-Wasiluk, Aneta (Journal of Public Governance, 2009)
The article is devoted to the analysis of the public goods theory, with particular regard to the discourse on the possibility to change the existing paradigm of the public sector economics. The study is divided into the following parts: a) nature of public goods, b) the free-rider paradox – are economists ethical nihilists?, c) efficient government as a public good, d) normative and positive theory of public goods, e) economics of the public sector – attempt to create a new paradigm. Each of the parts is a separate thread related to the existing theory of public goods. The author concludes that we are witnessing a change of the existing paradigm of public sector economics, within the framework of which a new scientific subdiscipline, economics of the public-private partnership, is created.